Synthesis of Amidine Derivatives by Intermolecular Radical Addition to Nitrile Groups of AIBN Derivatives - Su, Min; Zhu, Nengbo; Chiou, Mong-Feng; Bao, Hongli (Synlett, 2021)
A synthesis of amidine derivatives through intermolecular addition of nitrogen-centered radicals to nitriles is reported. Experimental studies and density functional theory calculations were conducted to probe the mechanism of this reaction. The results suggest that the alkyl nitriles are activated by attracting chlorine atoms and are subsequently attacked by nitrogen-centered radicals, resulting in the intermolecular radical addition of nitriles to amidines.
Keywords: amidines; nitriles; catalyst-free reaction; nitrogen-centered radicals; intermolecular radical addition